Determinasi Pola Asuh Orang Tua terhadap Perilaku Bullying Peserta Didik SMP - Meysa Putri, Alvina; Dianto, Mori; Chandra, Yasrial (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This research is motivated by the phenomenon of high parental parenting patterns on bullying behavior in students. The purpose of this study is to describe: 1. Description of Parenting Patterns in Class VIII SMP N 14 Dumai. 2. Description of Bullying Behavior in Students in Class VIII SMP N 14 Dumai. 3. The Influence of Parenting Patterns on Bullying Behavior in Students in Class VIII SMP N 14 Dumai. This study used a quantitative research method of simple linear regression analysis. The population was 243 with a purposive sampling technique with a sample size of 151. The instrument used in this study was a questionnaire. Data analysis in this study used percentages and simple linear regression. The results of this study are: 1. Description of parental parenting patterns in Class VIII SMP N 14 Dumai is in the low category. 2. Description of bullying behavior in students in Class VIII SMP N 14 Dumai is in the low category. 3. There is a significant influence between parenting styles on bullying behavior in students in grade VIII of SMP N 14 Dumai. In other words, the hypothesis is accepted that there is an influence of parenting styles on students' bullying behavior of 78. The results of this study recommend that students can build good relationships with their parents because this has been proven to have a positive influence on bullying behavior. Emotional intelligence abilities, especially in recognizing and managing one's emotions, because this has been proven to have a positive influence on the smoothness of interpersonal communication.